'Physician advocates': a novel strategy for improving the value of hospital care by employing hospitalists part time to support non-hospitalist physicians. Issue 1 (1st January 2022) - Van Groningen, Nicole; Mosenifar, Zab; Sax, Harry C.; Fridman, Rachel; Kim, Sungjin; Nuckols, Teryl K.
ABSTRACT: Background and Objective: At many hospitals, private-practice physicians still admit their own patients and are accustomed to autonomy in clinical practice. This creates challenges for hospital's efforts to improve the efficiency, quality, and value of care. Experienced inpatient-focused physicians – 'Physician Advocates' – could act as liaisons between private practitioners and the fast-paced inpatient microsystem. Methods: We conducted a controlled pre-post ('differences-in-differences') analysis at an academic medical center where private-practice physicians care for about 40% of medical inpatients and hospitalist groups care for 60%. In the intervention, 'Physician Advocates' participated in daily multidisciplinary 'Progression of Care Rounds, ' offering suggestions to increase care quality for private-practice physicians' patients. Controls were cared for by a large, well-established hospitalist group, which convened separate, unchanged multidisciplinary rounds. Outcomes were length of stay (LOS; primary outcome), 30-day readmissions, and inpatient mortality. Results: In a risk-adjusted analysis of 31, 632 medical inpatients, LOS declined by 4 hours more from the baseline period to the post-intervention period in the intervention group relative to the control group (ratio: 0.96, 95% CI: 0.93–0.99, p = 0.004). Readmissions declined 22% more in the intervention group (OR: 0.78, 95% CI: 0.63–0.97, p = 0.023). Mortality was unchanged (OR: 1.23, 95% CI: 0.78–1.93 p-value = 0.378). Conclusion: Among inpatients cared for by private practitioners, adding Physician Advocates to multidisciplinary rounds was associated with improved LOS and reduced readmissions – measures of efficiency and value. The Physician Advocates approach should be tested in diverse health systems because it allows hospitals to leverage the expertise of on-site clinicians while respecting the traditional private-practice care model, in which primary care physicians manage their hospitalized patients.